Statistical analysis of the wrestling world championships in Istanblu 2012 - Dokmanac, M.; Karadzic, P.; Doder, D. (International Journal of Wrestling Science, 2012)
World senior championship is most important wrestling event after the Olympic Games. For this reason, the analysis of the world senior championship is very important for all wrestlers and coaches. Statistical analysis of the final matches are of great importance for the current situation, and based on the analysis of wrestling technique and duration of the fight at some periods and matches, we can predict which way the wrestling world is going in the future. This analysis can help coaches to program tactical and technical preparation of athletes for the upcoming competition, which is based on the latest findings about the developmental direction of international wrestling.